EDUKASI BERNIAGA ERA DIGITAL BERBASIS NILAI ISLAM PADA DESA KADUMANEUH - Huda, Nurul; Rofi'i, Muhammad; Gani, Ariel Nian; Haryanti, Sri Chusri; Luhur, Irgi Alfariz; Ashilah, Nasywa Athaya (Universitas Islam 45 Bekasi, 2025)
The rapid development of digital technology has significantly transformed the business world, requiring young generations to adapt effectively. However, the use of technology without guidance from Islamic values poses the risk of unethical business practices that contradict the principles of Sharia. Therefore, this Community Service (PkM) program aims to provide education for the youth of Kadumaneuh Village to understand digital-era entrepreneurship while remaining grounded in Islamic values. The program was carried out through training sessions, counseling, and two-way discussions between facilitators and participants, designed with a participatory approach to ensure active engagement. The results indicate that participants gained a better understanding of Sharia-based digital business concepts, particularly concerning honesty, transparency, the prohibition of usury, and the importance of trustworthiness in online transactions. Furthermore, this activity fostered awareness among the youth to integrate digital literacy with Islamic ethics in their entrepreneurial practices. The implication of this program is the emergence of opportunities to develop ethical, religious, and sustainable digital entrepreneurship at the village level. The originality of this initiative lies in its integration of technological education with Islamic values within the context of rural community empowerment, which has rarely been conducted previously. Thus, this program provides a concrete contribution to strengthening the capacity of the younger generation in facing the challenges of the digital economy while remaining aligned with Islamic principles.